Organic Upconversion Imager with Dual Electronic and Optical Readouts for Shortwave Infrared Light Detection. (19th February 2021) - Li, Ning; Eedugurala, Naresh; Leem, Dong‐Seok; Azoulay, Jason D.; Ng, Tse Nga
Abstract: There remains a critical need for large‐area imaging technologies that operate in the shortwave infrared spectral region. Upconversion imagers that combine photo‐sensing and display in a compact structure are attractive since they avoid the costly and complex process of pixilation. However, upconversion device research is primarily focused on the optical output, while electronic signals from the imager remain underutilized. Here, an organic upconversion imager that is efficient in both optical and electronic readouts, extending the capability of human and machine vision to 1400 nm, is designed and demonstrated. The imager structure incorporates interfacial layers to suppress non‐radiative recombination and provide enhanced optical upconversion efficiency and electronic detectivity. The photoresponse is comparable to state‐of‐the‐art organic infrared photodiodes exhibiting a high external quantum efficiency of ≤35% at a low bias of ≤3 V and 3 dB bandwidth of 10 kHz. The large active area of 2 cm 2 enables demonstrations such as object inspection, imaging through smog, and concurrent recording of blood vessel location and blood flow pulses. These examples showcase the potential of the authors' dual‐readout imager to directly upconvert infrared light for human visual perception and simultaneously yield electronic signals for automated monitoring applications. Abstract : This work presents an organic upconversion imager with efficient electronic and optical dual‐readouts to detect infrared radiation to 1400 nm. The key to improving efficiency results from the incorporation of an interlayer that suppressed non‐radiative recombination. The single pixel imager combines photo‐sensing and display, enabling demonstrations such as simultaneous recordings of blood vessel location and blood flow pulses.